2009
DOI: 10.1302/0301-620x.91b5.21827
|View full text |Cite
|
Sign up to set email alerts
|

A common reference frame for describing rotation of the distal femur

Abstract: The understanding of rotational alignment of the distal femur is essential in total knee replacement to ensure that there is correct placement of the femoral component. Many reference axes have been described, but there is still disagreement about their value and mutual angular relationship. Our aim was to validate a geometrically-defined reference axis against which the surface-derived axes could be compared in the axial plane. A total of 12 cadaver specimens underwent CT after rigid fixation of optical track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
94
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 38 publications
(66 reference statements)
7
94
1
Order By: Relevance
“…In recent publications we reported detailed values on the distribution and means of knee alignment in the coronal and horizontal planes, diverging from previous assumptions that ruled for a long time [12,28]. However, a systematic understanding of the role of joint line orientation and its association with the development of malalignment and arthritis is lacking.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…In recent publications we reported detailed values on the distribution and means of knee alignment in the coronal and horizontal planes, diverging from previous assumptions that ruled for a long time [12,28]. However, a systematic understanding of the role of joint line orientation and its association with the development of malalignment and arthritis is lacking.…”
Section: Discussionmentioning
confidence: 59%
“…A systematic understanding of normal mean values and variance in the population is lacking. We have reported detailed values on the distribution and means of knee alignment in the coronal and axial planes [2,28]. In these studies, performed on asymptomatic young individuals, we found that a substantial proportion of the population (24%) has so-called constitutional varus, defined as coronal tibiofemoral mechanical alignment of more than 3°varus.…”
Section: Introductionmentioning
confidence: 99%
“…8,[10][11][12] In a CT-based kinematic cadaver study from 2009, 12 Victor et al used the dependent relationship between the transverse axis of the femur and tibia to explore the true, three-dimensional, rotational axis of the knee and found that of all the surface-derived landmarks, the patients with osteoarthritis and concluded that on average the PCL was only 1.68 internal rotation (IR) relative to the SEA. They identified a statistically significant difference in the relationship in different coronal plane alignments -1.08 in the varus knee, 2.18 in the neutral knee, and 2.68 in the valgus knee.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of these anatomical landmarks has to be critically discussed especially concerning their intra-and inter-observer reproducibility [31,61,74] . Greatest inter-and intraindividual variability was found for the Whiteside line, followed by the TEA [71] . Yan et al [74] found the maximum potential errors for TEA and Whiteside line to be 13 ° (3 ° internal rotation to 10 ° external rotation) and 24 ° (16 ° internal rotation to 8 ° external rotation), respectively.…”
Section: Rotational Alignmentmentioning
confidence: 93%